ANALISIS PENGARUH BUDAYA ORGANISASI, KOMPENSASI, DAN KEPUASAN KERJA TERHADAP TINGKAT TURNOVER KARYAWAN PT. YUASA BATTERY INDONESIA – TANGERANG - Harjoyo, Harjoyo (Jurnal Sekretari Universitas Pamulang, 2015)
ABSTRACT  PATH   ANALYSIS    OF    ORGANIZATIONAL    CULTURE,    COMPENSATION   AND    JOB SATISFACTION ON EMPLOYEES TURNOVER OF YUASA BATTERY INDONESIA, CO,-LTD.-TANGERANG. The study attempted to examine a phenomena and to gain empirical evident, as well as to get a brief data on the influence of organizational culture, compensation and job satisfaction on employee turnover. The study applied descriptive and inductive of multivariat regresion method itâ€™s include 94 respondents as the samples. The samples were selected through proporsionate stratified sampling. The statistical tool were used is SPSS 17 software as the means to examine the data. The findings could be concluded as follows: (1) There was positive effect from all independent variables toward employee turnover within value influence 80,9%. (2) The results of this research indicated that job satisfaction was the greatest affecting to the employee turnover was as much as 59.1%. (3) Meanwhile there are positive influence of organizational culture was equal to 26.7%. (4) Then there are positive affecting of compensation was equal to 12.6%. Based on the analysis of the conclusions and implications of this research, there are several suggestions as follows:(1) Based on the calculation results of the questionnaire, organizational culture variables (X1) which consists of 4 dimensions and 12 indicators, dimensions of employee engagement have a presentation of the most low at 48.94%. It should be a concern for the company improve employee engagement as a problem-solving discussion, provides an opportunity to move forward, and so on. (2) The compensation variable (X2) consisting of 4 dimensions and 12 indicators, dimensions of the facility have a presentation that is equal to 51.33% lower. It should be a concern for the company improve employee facilities required such as parking areas, parks, sports facilities, so that employees feel comfortable in the company area. (3) The Job satisfaction variables (X3) which consists of 4 dimensions and 16 indicators, job security dimension has the lowest presentation that is equal to 52.38%. It is recommended that companies pay more attention to health and safety, and social security so employees do not feel anxious in doing the job.(4) The Turnover variable (Y) consisting of 4 dimensions and 13 indicators, dimensions of the work environment has a presentation of the work value that is equal to 53.19%. This is not apart from polluting production processes and pollution and generate waste hazardous and toxic material. Although the company has done with the implementation of an Environmental Management System ISO 14001 but is still expected to increase in the control of potential environmental pollution and threats, so that not only the employees in the company that would avoid the risk of pollution and contamination of the surrounding community but also will feel calm and do not disturb the existenceof the c ompany. Kata Kunci: Budaya Organisasi, Kompensasi, Kepuasan Kerja, Tingkat Trun Over Karyawan